Antimicrobial susceptibility pattern of urine culture isolates in a tertiary care hospital of Jharkhand, India - Kumar, Akhilesh; Kumar, Rajiv; Gari, Manju; Keshri, Uma Shanker P.; Mahato, Sumit K.; Ranjeeta, Kumari (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Urinary tract infection (UTI) is one of the common infections encountered by the clinicians. Though a good number of antimicrobial agents are available, still UTIs have become difficult to treat due to development of resistance by the uropathogens. So, regional data regarding the common uropathogens and their sensitivity pattern is required to guide the clinicians to start empirical therapy while managing UTIs. The purpose of the study was to identify different species of microorganisms, along with their antimicrobial susceptibility pattern, causing urinary tract infection in outpatient and indoor patients at RIMS, Ranchi, Jharkhand. Methods: Observational study was conducted using urine culture and sensitivity reports collected retrospectively from records maintained in the department of Microbiology over a period from July 2016 to Feb 2017 in tertiary care hospital. Results: UTI was more common in females (57.74%) than in males (42.26%). Among the uropathogens isolated Escherichia coli (37.41%) was found to be the predominant organism followed by Klebsiella species (32.79%), Pseudomonas species (25.86%), and gram-positive bacteria Staphylococcus aureus accounted (3.92%) of total cases. The most common isolates were E. coli showed high sensitivity to amikacin (79.24%), followed by levofloxacin (77.21%) and gentamycin (62.26%). It was found to be resistant to norfloxacin (86%), nalidixic acid (86.76%) and cefotaxime (69.88%). Conclusions: Though various microorganisms are responsible for UTI. Escherichia coli species is the most common organism. Antimicrobial resistance has already emerged against many antibiotics, making empirical treatment of these infections challenging.